Exposing the Secrets of Two Well-Known Lactobacillus casei Phages, J-1 and PL-1, by Genomic and Structural Analysis - Dieterle, Maria Eugenia (Appl Environ Microbiol, 2014)
Bacteriophage J-1 was isolated in 1965 from an abnormal fermentation of Yakult using Lactobacillus casei strain Shirota, and a related phage, PL-1, was subsequently recovered from a strain resistant to J-1. Complete genome sequencing shows that J-1 and PL-1 are almost identical, but PL-1 has a deletion of 1.9 kbp relative to J-1, resulting in the loss of four predicted gene products involved in immunity regulation. The structural proteins were identified by mass spectrometry analysis. Similarly to phage A2, two capsid proteins are generated by a translational frameshift and undergo proteolytic processing. The structure of gene product 16 (gp16), a putative tail protein, was modeled based on the crystal structure of baseplate distal tail proteins (Dit) that form the baseplate hub in other Siphoviridae. However, two regions of the C terminus of gp16 could not be modeled using this template. The first region accounts for the differences between J-1 and PL-1 gp16 and showed sequence similarity to carbohydrate-binding modules (CBMs). J-1 and PL-1 GFP-gp16 fusions bind specifically to Lactobacillus casei/paracasei cells, and the addition of l-rhamnose inhibits binding. J-1 gp16 exhibited a higher affinity than PL-1 gp16 for cell walls of L. casei ATCC 27139 in phage adsorption inhibition assays, in agreement with differential adsorption kinetics observed for both phages in this strain. The data presented here provide insights into how Lactobacillus phages interact with their hosts at the first steps of infection.